Cardiac mast cell regulation of matrix metalloproteinase-related ventricular remodeling in chronic pressure or volume overload - Janicki, Joseph S; Brower, Gregory L; Gardner, Jason D; Forman, Mary F; Stewart, Jr, James A; Murray, David B; Chancey, Amanda L (Cardiovascular research, 2006)
The chronic elevation in ventricular wall stress secondary to ventricular volume or pressure overload leads to structural remodeling of the muscular, vascular and extracellular matrix components of the myocardium. While initially a compensatory response, the progressive hypertrophy and ventricular dilatation induced by this condition ultimately have a detrimental effect on ventricular function, resulting in heart failure. Fibrillar collagen provides the skeletal framework which interconnects the cardiomyocytes, thereby maintaining ventricular shape and size and contributing to tissue stiffness. Accordingly, these myocardial collagen fibers must be disrupted for ventricular dilatation, sphericalization and wall thinning to occur. The presence of an abundant, latent matrix metalloproteinase (MMP) population which coexists with myocardial fibrillar collagen has been documented. Thus, the potential for collagen degradation to exceed synthesis exists should there be significant activation of this latent MMP system. Mast cells are known to store and release a variety of biologically active mediators including TNF-alpha and proteases such as tryptase and chymase, which can induce MMP activation. Increased cardiac mast cell density has been implicated in the pathophysiology of human end-stage cardiomyopathy and experimental myocardial infarction, hypertension and chronic volume overload secondary to mitral regurgitation and aorto-caval fistula. The potential role of cardiac mast cells in activating MMPs, which then results in fibrillar collagen degradation and adverse myocardial remodeling secondary to chronic volume and pressure overload will be the subject of this review.